3D bone tissue growth in hollow fibre membrane bioreactor: implications of various process parameters on tissue nutrition. - Abdullah, N; Das, D; Ye, H; Cui, Z (2006)
New experimental evidence shows that hollow fibre membrane bioreactor (HFMB) may be applied to grow bulky bone tissues which may then be implanted into patients to repair skeletal defects. To design effective bone tissue engineering protocols, it is necessary to determine the quantitative relationships between the cell environment and tissue behaviour in HFMBs and their relationship with nutrient supply. It is also necessary to determine under what conditions nutritional limitations may occur and, hence, may cause cell death. These require that the appropriate bioreactor conditions for generating neotissues, and the nutrient transfer behaviour and chemical reaction during cell growth and extracellular matrix formation are studied thoroughly. In this paper, we aim to use an existing mathematical framework to analyse the influence of various relevant parameters on nutrient supply for bone tissue growth in HFMB. We adopt the well-known Krogh cylinder approximation of the HFMB. The model parameters (e.g., cell metabolic rates) and operating conditions for the mathematical model have been obtained from, or correspond to, in-house experiments with the exception of a few variables which have been taken from the literature. The framework is then used to study oxygen and glucose transport behaviour in the HFMB. Influence of a number of important process parameters, e.g., reaction kinetics, cell density, inlet concentration of nutrients, etc, on the nutrient distributions have been systematically analysed. The work presented in this paper provides insights on unfavourable system designs and specifications which may be avoided to prevent mass transfer limitations for growing bone tissues in HFMB.